The Possibility of Applying Artificial Intelligence in Civil Proceedings - Gharslyan, Ashkhen (Bulletin of Yerevan University C: Jurisprudence, 2023)
In the article, the author referred to the possibility of using artificial intelligence in judicial procedures. For this purpose, first of all, the author revealed the essence of artificial intelligence algorithms, the advantages and disadvantages of their application, and identified the possible legal areas in which these algorithms can be applied. The ability of artificial intelligence algorithms in predicting justice has been discussed in more detail. At the same time, the article presented the five principles provided by the European Ethical Charter on the Use of Artificial Intelligence in Judicial Systems and their Environment adopted by the European Commission for the Efficiency of Justice in 2018, which should have guiding significance in the design and implementation of artificial intelligence algorithms in judicial procedures.